EFFECT OF PARITY ON THE PERFORMANCES OF BRAHMAN CROSS COWS AND THEIR CALVES KEPT UNDER INTEGRATED CATTLE AND OIL PALM PRODUCTION - Kurniawan, Akhmad; Ihsan, Muhammad Nur; Amertaningtyas, Dedes; Irsyammawati, Artharini; Andri, Faizal; Isnaini, Nurul (Jurnal Kedokteran Hewan, 2025)
The integrated cattle and oil palm production is currently recognized as one of the potential strategies to fulfill national meat demand in Indonesia. This study investigated the effect of parity on the performances of Brahman cross cows and their calves kept under integrated cattle and oil palm production. The cows receive natural mating with the provision of Brahman cross bulls (bull:cow ratios of 1:20). Data of body weight and body condition score of 300 cows were recorded after parturition. Data of body weight and weaning weight of their 600 calves (300 calves of each of parity 1 and 2) were also included in this study. Data were compared between parity 1 and 2 by using paired Wilcoxon signed-rank test. The results demonstrated that the cows in parity 2 had higher (P0.001) body weight and body condition score than those in parity 1. Parity 2 also increased (P0.001) birth and weaning weight of calves as compared to parity 1. It could be concluded that parity has a significant contribution to the performance of Brahman cross cows and their calves, with parity 2 provides better performance than parity 1.